Pengaruh Media Interaktif Educaplay terhadap Hasil Belajar IPA Peserta Didik Kelas V Sekolah Dasar - Ge’e, Ros Suryaningsih; Dahlan, Zaini (Jayapangus Press, 2025)
Science education in elementary schools requires innovative learning media to improve student learning outcomes. One of the interactive media that can be used is educaplay media, which offers various educational game-based activities. However, the effectiveness of this media in improving students' science learning outcomes in elementary schools still needs further research. Therefore, this study aims to analyze the effect of using educaplay interactive media on the science learning outcomes of fifth grade students. Quasi-experimental design was applied as a method of this research with nonequivalent control group design as its design. The research sample consisted of 70 students, who were divided into two groups, namely, the experimental group using educaplay media and the control group using conventional media. The research instruments were in the form of learning outcome tests and documentation. The data obtained were analyzed using normality tests, homogeneity tests, and hypothesis tests through independent sample t-tests. The results of the study showed that there were significant differences between the experimental group and the control group. The results of the independent sample t-test showed a sig value (2-tailed) = 0.001 <0.05, which means that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Thus, the use of educaplay media has been proven to have a positive effect on students' science learning outcomes. Students who learn with educaplay media show better conceptual understanding and are more motivated than students who learn using conventional media. In conclusion, educaplay as an interactive learning media can improve the science learning outcomes of grade V elementary school students. Therefore, its use can be considered as an alternative in science learning to increase student involvement and understanding.